2018
DOI: 10.1515/hsz-2018-0178
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X protein promotes proliferation of hepatocellular carcinoma cells by upregulating miR-181b by targeting ING5

Abstract: Hepatitis B virus X protein (HBx) played a key role in the development of hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). Emerging evidence has demonstrated that miR-181b and the inhibitor of growth protein 5 (ING5) participated in the pathophysiological process. However, the regulatory mechanism of HBx remained unknown. The expression of miR-181b and ING5 in HCC tissues and cell lines were examined using quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting. Cell viab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…20 As an important co-factor of p53, the ING tumor suppressor family regulates DNA repair, apoptosis and cell cycle. 21 - 23 All ING proteins include plant homologous domains (PHD), which have been identified as binding motifs of DNA, RNA and proteins that bind histones in a methylated sensitive manner to regulate chromatin structure. 7 , 24 , 25 Thus they are closely related to the pathogenesis of different types of cancer as well as tumor growth (angiogenesis) and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…20 As an important co-factor of p53, the ING tumor suppressor family regulates DNA repair, apoptosis and cell cycle. 21 - 23 All ING proteins include plant homologous domains (PHD), which have been identified as binding motifs of DNA, RNA and proteins that bind histones in a methylated sensitive manner to regulate chromatin structure. 7 , 24 , 25 Thus they are closely related to the pathogenesis of different types of cancer as well as tumor growth (angiogenesis) and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…miR-331-3p could promote proliferation of HCC cells by targeting ING5, which was strengthened by hepatitis B virus (HBV) ( Cao et al, 2015 ). HBx protein of HBV accelerated the proliferation of HCC cells by up-regulating miR-181b to target ING5 ( Xie et al, 2018 ). In neuroblastoma cells, ING5 is a negatively- regulated target gene of miR-376c-3p ( Zhang et al, 2019 ), and SAHA down-regulates miR-196-b and miR-543 expression to facilitate the translation of ING5 protein ( Wu et al, 2018 ).…”
Section: The Regulation Of Ing5 Expressionmentioning
confidence: 99%
“…Various miRNAs are involved such as miR-196a in pancreatic cancer (140), miR-1307 in ovarian cancer (32), miR-24 in breast cancer (141) and miR-27-3p in osteosarcoma (142). In addition, two reports have shown that miR-331-3p and miR-181b both of which target the 3'UTR of ING5 are upregulated by the hepatitis B virus protein X (143,144). This overexpression can promote the proliferation of hepatocarcinoma cancer cells.…”
Section: Accepted Manuscriptmentioning
confidence: 99%